From Needs Analysis to Listening Instruction: A Mixed-Methods Study on EFL Students’ Comprehension and Engagement - Wiwied Pratiwi; Suhono Suhono (CV. Creative Tugu Pena, 2025)
Listening remains one of the most challenging skills in English as a Foreign Language (EFL) learning, particularly at the tertiary level, where learners are required to construct meaning beyond surface-level linguistic recognition. This study aims to explore the effectiveness of needs-based listening materials in enhancing students’ comprehension and engagement. A mixed-methods sequential design was employed, integrating quantitative and qualitative data. Quantitative data were collected through pre-test and post-test measures and analyzed using a paired sample t-test, while qualitative data were obtained through classroom observations and interviews to examine students’ engagement and learning experiences. The findings reveal a statistically significant improvement in students’ listening performance, with mean scores increasing from 58.40 to 72.85 (p < 0.05) and a large effect size. This improvement reflects substantial development in macro listening skills, particularly in identifying main ideas and constructing overall meaning. These quantitative results are further supported by qualitative evidence indicating high levels of student engagement, as demonstrated by active participation (82%), sustained attention (85%), and increased learning motivation (81%). The findings suggest that needs-based materials provide more relevant and accessible input, thereby facilitating both cognitive and affective engagement in the listening process. This study contributes to the literature by integrating needs analysis with a specific focus on macro listening skills within a mixed-methods framework. It not only demonstrates the effectiveness of instructional materials quantitatively but also elucidates the underlying mechanisms of learning improvement qualitatively. The study offers important pedagogical implications for designing contextually relevant and learner-centered listening materials in EFL higher education contexts